Volume effect on the extraction of speed of sound in high-energy nucleus-nucleus collisions - Sun, Jing-An; Yan, Li (Physics letters. B, 2025)
The determination of the speed of sound in quark-gluon plasma is a crucial aspect of understanding the properties of strongly interacting matter created in relativistic heavy-ion collisions. In this study, we investigate the impact of initial-state fluctuations on the extraction of the speed of sound in a quark-gluon plasma in the ultra-central collisions. By employing the TRENTo model for simulating initial conditions, we demonstrate that these fluctuations lead to sizable volume effect, which in turn corrects the measured values of the speed of sound. Once the volume corrections are systematically taken into account, the extracted speed of sound approach the physical value, while dependence on model parameters is substantially suppressed.